The Language of Cigar Use: Focus Group Findings on Cigar Product Terminology - Dickinson, Denise M. (Nicotine Tob Res, 2016)
INTRODUCTION: The consumption of cigar products has increased since 2000. The multiple product types within this category, combined with the varied language with which consumers refer to them, present challenges for accurately assessing the prevalence of cigar product use. Surveillance is also complicated by the fact that these products can be used to smoke marijuana, as “blunts”— cigars in which the tobacco is removed and replaced with marijuana. Few studies exist regarding the language and terminology used to describe these products. METHODS: Sixteen focus groups were conducted in fi cities in the United States between March and May of 2014. Participants (N = 123) included adults who had used cigars, cigarillos, or little cigars in the past 30 days. A semi-structured moderator guide was used to gather data on the terms used to identify cigar product subtypes and the language used to describe the products and their use. RESULTS: Participants used a variety of terms for each product subtype. Brand names were often used, as well as slang terms, including terms describing cigars modified for marijuana use. Some subtypes were less likely than others to be considered “cigars.” Participants had mixed opinions about whether users of cigar products are “smokers.” CONCLUSIONS: Users of cigar products may classify or label products differently from researchers and policy makers, and many refer to their product by brand name or a slang term. These fi have implications for future research, instrument design, and public health messaging about cigar products. IMPLICATIONS: This study adds to the body of evidence highlighting the challenges for measurement and surveillance of non-cigarette tobacco products, including cigars. Findings illustrate the myriad terms used by consumers to describe their use of cigar product subtypes, as well as the complexity of distinguishing between use of cigar products as intended, versus as a vehicle for smoking marijuana. Future research aimed to enhance specifi of cigar use measures will enable policy-makers and public health practitioners to more fully characterize prevalence and patterns of use by cigar subtype.